Design and Development of BIW Fixture for Front Windshield With Manual Loading, Unloading & Welding - Khandekar, Kumar S.; Bhardiya, S G.; S. Mule, Prathmesh; Koli, Ashish; Madne, Akshay (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
Today’s welding fixtures for the automotive industry are crucial for auxiliary welding. The body of the car is welded together using numerous intricate sheet sections and additional support pieces. The welding fixture’s supporting role is an essential element in this project’s process. The phrase “Body in White” (BIW) is frequently used in the automotive industry to refer to the sheet metal-welded construction of the car. Automobile BIW is currently constructed of steel and an aluminum alloy. The BIW component is joined using a variety of metal joining techniques, such as MIG welding, to create a welded metal shell known as Body in White. We need to construct a BIW fixture in order to weld it together. Fixtures are used to firmly anchor in a particular spot or to assist work, assuring the interchangeability and conformance of all parts produced using the fixture. The placement of the spot welds is to be determined in the welding fixture design. The clamps, locators, rest mylar, riser, clamp cylinder are included in the location and orientation of the fixture. At the setup planning stage, fixture design is crucial. The fixture setup is done manually in the current design due to the surface finish and precision of the machined pieces. Software called Catia is used to design the fixture.